2019
DOI: 10.21037/jss.2019.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Current state of minimally invasive spine surgery

Abstract: Newer navigation protocols that rely on intraoperative CT registration have improved the accuracy of imaging models and allowed surgeons to rely less on fluoroscopy. Despite concerns regarding ionizing radiation exposure to the patient, use of CT navigation systems was found to reduce radiation exposure by more than 90% compared to traditional fluoroscopic guided percutaneous surgical techniques (1). Furthermore, the surgeon's exposure to radiation is almost eliminated, as the surgeon does not need to be close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
78
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 56 publications
0
78
0
1
Order By: Relevance
“…Even though fluoroscopy-guided pedicle screw fixation has demonstrated high accuracy, radiation exposure to surgeons and patients has been an issue. The application of CT-based navigation systems might reduce the risk of radiation exposures to surgeons and patients by more than 90% during the procedures while providing much higher accuracy for pedicle screw fixation [ 3 , 33 , 34 ]. Given MISS, especially MI-TLIF and MI-LLIF, are typically performed with percutaneous pedicle screw fixation, the application of navigation systems provides high reliability and safety.…”
Section: Minimally Invasive Spine Surgery Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Even though fluoroscopy-guided pedicle screw fixation has demonstrated high accuracy, radiation exposure to surgeons and patients has been an issue. The application of CT-based navigation systems might reduce the risk of radiation exposures to surgeons and patients by more than 90% during the procedures while providing much higher accuracy for pedicle screw fixation [ 3 , 33 , 34 ]. Given MISS, especially MI-TLIF and MI-LLIF, are typically performed with percutaneous pedicle screw fixation, the application of navigation systems provides high reliability and safety.…”
Section: Minimally Invasive Spine Surgery Technologymentioning
confidence: 99%
“…Given MISS, especially MI-TLIF and MI-LLIF, are typically performed with percutaneous pedicle screw fixation, the application of navigation systems provides high reliability and safety. Many studies have reported that the current CT image-based navigation systems are highly reliable and thus can be applied to most MISSs to reduce operation-related complications, including reoperation rates [ 3 , 34 ]. One remaining problem is the navigation system cost, which should be balanced out as its usage rate increases.…”
Section: Minimally Invasive Spine Surgery Technologymentioning
confidence: 99%
See 3 more Smart Citations